Distinct Expression Levels of ALS, LIP, and SAP Genes in Candida tropicalis with Diverse Virulent Activities - Yu, Shuanbao; Li, Wenge; Liu, Xiaoshu; Che, Jie; Wu, Yuan; Lu, Jinxing (Frontiers in Microbiology, 2016)
Candia tropicalis is an increasingly important human pathogen, causing nosocomial fungemia among patients with neutropenia or malignancy (Guinea, 2014). However, limited research has been published concerning its pathogenicity. Based on the phenotypes of C. tropicalis in our previous study, we selected nine representative strains with different activities of virulence factors (adhesion, biofilm formation, secreted aspartic proteinases and hemolysins), and one reference strain, ATCC750. The present study aimed to investigate the filamentation ability, the expression of virulence genes (ALST1-3, LIP1, LIP4 and SAPT1-4) and the cell damage of C. tropicalis strains with diverse virulences. C. tropicalis exhibited strain-dependent filamentation ability, which was positively correlated with biofilm formation. Reverse transcriptase PCR analysis showed that the ALST3 and SAPT3 genes had the highest expression in their corresponding genes for most C. tropicalis. The expressions of virulence genes, except ALST3 on polystyrene, were upregulated compared with growth in the planktonic and on human urinary bladder epithelial cell line (TCC-SUP) surface. Clustering analysis of virulence genes showed that isolates had a high biofilm forming ability on polystyrene formed a group. Lactate dehydrogenase assays showed that the cell damage induced by C. tropicalis markedly increased with longer infection time (24 and 48 h). Strain FXCT01, isolated from blood, caused the most serious cell damage; while ZRCT52, which had no filamentation ability, caused the least cell damage. Correlation analysis demonstrated significant correlation existed between adhesion on epithelial cells or the expression of ALST2-3 and cell damage. Overall, our results supported the view that adhesion and filamentation may play significant roles in the cell damage caused by C. tropicalis.